The Learning Stages of Ngroncongi/Undul usuk: Achieving the Original Solo Keroncong Singing Style - Sukmayadi, Yudi; Supiarza, Hery; Andini, Mustika (Malaysian Journal of Music, 2022)
The hegemony of advanced keroncong figures in keroncong singing has made the Solo keroncong singing style more recognised by the wider community with its lilting characteristics. However, for the Surakarta people (Solo), there is something more essential than that, namely ngroncongi, also known as undul usuk. This term is often given to keroncong singers as an assessment of the quality of their singing. Hence, this research aims at identifying and describing undul usuk and its achievement process by employing descriptive qualitative methods. Observation, interviews, and documentation studies were used to collect the data, while the triangulation technique was used to test the data’s validity. The findings show that the undul usuk concept is a sub-concept of the ngroncongi basic concept. There are various hierarchical stages in the achievement of Solo keroncong singing, which consist of the beginner stage, the average stage, the skilled stage, the specialist stage, and singing ngroncongi as the highest achievement or expert stage. To achieve this, some rules and tips need to be followed, which requires effort and time. Singers are required to be effortless in aligning skills, thoughts, and feelings. This study manifests a society that preserves the essence of keroncong singing through development and preservation dualism.The novelty of this research is on how it can be used as a reference for the performer and connoisseurs of keroncong music.